Zonificación de susceptibilidad a deslizamientos en zonas urbanas de las parroquias: San Sebastián de Sígsig, Guel y Cutchil, cantón Sígsig, provincia Azuay. - Plasencia Chullca, Pamela Carolina (2023)
This research is carried out the zoning of landslide susceptibility in urban areas of the parishes: San Sebastian of Sigsig, Guel and Cutchil of Sigsig canton of the province of Azuay by using the Geographic Information System or GIS where the variables that generate landslides were processed from the survey of information in office and field, in which the variables were prioritized as follows: geomorphological units, lithology, slopes, vegetation coverage and precipitation; likewise, the landslide inventory was elaborated to correlate the results. In order to obtain the landslide susceptibility zoning map, the methodology of Saaty´s Hierarchical Analytical Process (1980) was applied, which is a semi-cranial multicriteria method that allows analyzing the variables that generate landslides based on their incidence in the terrain. All the variables were then processed in ArcGIS 10.5 software to obtain the landslide susceptibility map, which was correlated with the landslide inventory, categorizing susceptibility into five classes: extremely low, low, moderate, high and extremely high. Key words: susceptibility, landslides, GIS, Saaty, Sígsig, intrinsic variables, extrinsic variables.